2012
DOI: 10.1007/s00384-012-1445-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inositol hexaphosphate on the expression of selected metalloproteinases and their tissue inhibitors in IL-1β-stimulated colon cancer cells

Abstract: IntroductionMatrix metalloproteinases (MMPs) have repeatedly been shown to play a very active role in extracellular matrix degradation associated with tumor invasion and metastasis. Tissue inhibitors of MMPs (TIMPs) are well-known for their ability to inhibit MMP activity thereby inhibiting malignant progression. Inositol hexaphosphate (IP6 phytic acid) has been recognized to have both preventive and therapeutic effects against various cancers including that of colon. In in vitro studies, IP6 has been demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…InsP 6 possesses antiproliferative activities and has therefore been proposed as an antitumor agent (Vucenik et al, 2005;Tian and Song, 2006;Agarwal et al, 2009;Kapral et al, 2012;Deliliers et al, 2002;Singh et al, 2003). In the same way, Ni(II) has been described as an important cytotoxic agent and apoptosis inductor (Ada et al, 2010;Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…InsP 6 possesses antiproliferative activities and has therefore been proposed as an antitumor agent (Vucenik et al, 2005;Tian and Song, 2006;Agarwal et al, 2009;Kapral et al, 2012;Deliliers et al, 2002;Singh et al, 2003). In the same way, Ni(II) has been described as an important cytotoxic agent and apoptosis inductor (Ada et al, 2010;Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…The InsP 6 influences constitutive expression of metalloproteinase, MMP and TIMP (tissue inhibitors of MMPs) genes and downregulates IL-1β stimulated transcription of some of these genes. InsP 6 exerts its anti-metastatic activity through modulation of MMP and TIMP genes expression to prevent cancer cell migration and invasion (Kapral et al, 2012). Physiological intestinal concentrations of InsP 6 may have an Toxicology in Vitro 29 (2015) …”
Section: Introductionmentioning
confidence: 99%
“…We also observed TIMP-2 upregulation in BRAF and KRAS-mutant ACF, although the effect of TIMP-2 on tumor progression is less well-defined (40). Some studies have correlated high levels of TIMP-2 with an adverse prognosis (41,42), while other studies have observed an opposite effect (4345). The general consensus, however, is that overexpression of TIMP family proteins elicit effects on ECM turnover and facilitates formation of the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…A standard curve method was used to quantify the RT-qPCR results for hTERT, ACD, DKC1 and GAPDH (24,25). Commercially available β-actin cDNA standards (TaqMan ® DNA Template Reagent kit; Applied Biosystems) were used at 0.6, 1.2, 3.0, 6.0 and 12.0 ng/µl to simultaneously detect the expression profile of each of the target genes.…”
Section: Methodsmentioning
confidence: 99%